2004
DOI: 10.1515/jbcpp.2004.15.3-4.277
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Clinicopathological Changes Induced by Bungarus coeruleus Venom in a Rat Model

Abstract: Bungarus coeruleus, a common venomous snake allied to the cobra, is responsible for most envenomations in India. This study examines the pathological effects of B. caeruleus venom and the associated biochemical changes in a rat model. Increased serum aspartate aminotransferase (48%), creatine kinase (30%), and lactate dehydrogenase (6%) were detected after a sublethal dose of 25 microg/kg of B. caeruleus venom was injected intramuscularly into rats observed for 180 min. The venom induced hyperglycemia and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…A previous study in India using B. caeruleus venom, has demonstrated haemorrhage and necrosis of proximal tubules of the kidney and petechial haemorrhages in the myocardium (Kiran et al, 2004) in addition to findings similar to the present study.…”
Section: Bungarussupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study in India using B. caeruleus venom, has demonstrated haemorrhage and necrosis of proximal tubules of the kidney and petechial haemorrhages in the myocardium (Kiran et al, 2004) in addition to findings similar to the present study.…”
Section: Bungarussupporting
confidence: 92%
“…Degeneration, necrosis and regeneration of tubular epithelial cells are seen in renal tubules. Interstitial oedema, cellular infiltration, arteritis, thrombophlebitis, congestion, infarction and cortical necrosis have also been observed (Sitprija, 2006;Kiran et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Cytoplasmic vacuolization, infiltration and congestion of blood vessels were major changes in cardiac tissue. The findings of current study are almost consistent with previous observations ( Al-Mamun et al, 2015a ; Kiran et al, 2004 ; Nanayakkara et al, 2009 ). However, in this study, clear and broad range images are presented for histopathological tissue sections of B. caeruleus envenomed mice.…”
Section: Discussionsupporting
confidence: 94%
“…8–10 The morphological changes in the kidney in fatal snakebite cases are vividly elaborated in texts of forensic pathology. Studies have shown renal histological changes 13,14 induced by krait (neurotoxic) venom in animal model. We devised a scoring system on the basis of the renal pathology found at autopsy in fatal snakebite cases.…”
Section: Discussionmentioning
confidence: 99%